Case studies - (:unkn) unknown (Nova Science Publishers, Inc., 2021)
Case studies help both pharmacy students and pharmacists apply their theoretical knowledge to practice. The aim of case studies is to identify solutions to drug-related problems by applying pharmacology and other pharmaceutical sciences. Case studies in oncology pharmacy education also guide clinical pharmacists regarding the determination and management of drug-induced toxicities, especially the preparation of chemotherapy orders. In this paper, different chemotherapy protocols frequently encountered in oncology clinics are presented as case studies. In conclusion, issues related to chemotherapy preparation and administration, dose calculations, premedication drugs, and adverse effects of chemotherapy protocols are discussed through case studies. © 2021 Nova Science Publishers, Inc. All rights reserved.
Keywords: Case studies; Chemotherapy preparation; Chemotherapy protocols